PERANCANGAN ENTERPRISE ARCHITECTURE PROSES PELATIHAN KERJA - Herawati, Dewi; Gondokary, Yudi Satria (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2014)
One of the components of enterprise architecture (EA) is information architecture (IA), which has three elements, those are people, process, and technology. The research was conducted using the variables on the process elements involving people and technology elements. This research discusses the designing of information architecture model of vocational training process at the Balai Besar Pengembangan Latihan Kerja Dalam Negeri (BBPLKDN) Bandung. Stages of the research are using qualitative approach method. COBIT 5 and TOGAF framework are used as the references during the analysis and designing. The analysis tool used is the consolidation of BSC and CSF. Validation of the research result is done by triangulation method to the theory, vocational training regulatory/policy, and the BBPLKDN Bandung need. The conclusion from this research is that the information architecture model of vocational training process in BBPLKDN Bandung is affected by elements of people, process, and technology in the scope of enterprise architecture, with reference to the results of BSC and CSF consolidation.